2022
DOI: 10.3390/electronics11030496
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Emotion Recognition Out of the Lab into Real Life: Recent Advances in Sensors and Machine Learning

Abstract: Bringing emotion recognition (ER) out of the controlled laboratory setup into everyday life can enable applications targeted at a broader population, e.g., helping people with psychological disorders, assisting kids with autism, monitoring the elderly, and general improvement of well-being. This work reviews progress in sensors and machine learning methods and techniques that have made it possible to move ER from the lab to the field in recent years. In particular, the commercially available sensors collecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 92 publications
(99 reference statements)
0
18
0
1
Order By: Relevance
“…The word is connected to other nodes through dependencies. In RNN, what is computed from all its children using a weight matrix is a vector representation of each node [27].…”
Section: Sentiment Category Outputmentioning
confidence: 99%
“…The word is connected to other nodes through dependencies. In RNN, what is computed from all its children using a weight matrix is a vector representation of each node [27].…”
Section: Sentiment Category Outputmentioning
confidence: 99%
“…Research with neurophysiological sensors [ 12 , 13 ] has begun to aid in monitoring schizophrenia [ 14 , 15 ], Parkinson’s’ disease [ 16 ], traumatic brain injury [ 17 ], physiological signals [ 18 ], cognitive function [ 19 ], epileptic seizures [ 20 ], alcoholism [ 21 ], brain tumors [ 22 ], brain cancer [ 23 ], mental stability [ 24 ], personality [ 25 ], eye tracking [ 26 ], and many other phenomena. Moreover, studies conducted on EEG data processing have identified human emotions with exceptional accuracy [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. These studies are the backbone of the growing number of emotional recognition applications, and because of their far-reaching applications, the societal impact of enhancing their efficiency, accuracy, and precision cannot be overstated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rapid development and increasingly widespread use of artificial intelligence technologies has led to a significant increase in interest and development of systems that automatically recognize affective states. These systems are designed to recognize, accurately interpret, and respond to the recognized emotional states of the communicating individual [ 2 , 3 , 4 , 5 , 6 ]. There is an entire class of solutions called multimodal-based affective human–computer interaction that enables computer systems to recognize specific affective states.…”
Section: Introductionmentioning
confidence: 99%